Histomorphological Analysis of Placental & Umbilical Cord Blood Vessels in Gestational Diabetes Mellitus - Anum Hafeez Dogar; Shagufta Nasreen; Samia Shahbaz; Amber Ilyas; Noor Ijaz; Sana Fatima Dogar (Liaquat National Journal of Primary Care)
Background: Gestational Diabetes Mellitus (GDM) is a primary health issue in our society. Diabetes during pregnancy presents various challenges that can impact the growth and development of the fetus, relying on the healthy functioning of the placenta and umbilical cord. Objective: In this study, an evaluation of histomorphological changes in umbilical cord was done in gestational diabetes mellitus. Methods: This comparative cross-sectional study comprised 58 subjects, having two groups: Group A consisted of 29 healthy subjects, and Group B of 29 gestational diabetes mellitus patients. The study duration was from July 2020 to July 2021. It was conducted by keeping the declaration of Helsinki as an ethical guide for research involving human subjects at Lahore General Hospital, Lahore, and the Experimental Research Laboratory of Postgraduate Medical Institute (PGMI) Lahore. History and examination were done regarding gestational diabetes mellitus. Umbilical cords were collected at the time of delivery and washed with normal saline. A gross examination was done, and samples were preserved for histomorphology. Results: The diameter of the umbilical cords was significantly increased in Group B (case) as compared to Group A (control). There was no significant difference in the number of false knots in the two groups. Histologically, there was endothelial disruption of the umbilical artery and congestion of the umbilical vein in Group B, but no such increase in Group A. Conclusion: This study showed that there were significant histomorphological changes in GDM umbilical cords